Electrochemical Treatment of Slaughterhouse and Dairy Wastewater: Toward Making a Sustainable Process - Salazar-Gonzalez, R; Sandoval, A; Sandoval, A (Elsevier B.V., 2021)
The industrial processing of meat and dairy production uses large amounts of fresh water, therefore, generates a significant volume of wastewaters. The treatment of these effluents has been performed using different technologies from biological to electrochemical advanced oxidation processes. Under the circular economy concept, the lack of available freshwater resources has increased the interest in reusing wastewater from slaughterhouses, and even in the recovering of by-products. This article reviews the application of electrochemical treatments to slaughterhouse and dairy wastewaters. In addition, an overview of added-value products and energy recovery from these industrial wastewaters is also presented with future perspectives. © 2020 Elsevier B.V.